Analysis of the validity, reliability and differentiability of the interpersonal reactions inventory of Grossarth - Maticek and Eysenck in entering students of UNALM - Aparicio Pereda, Ana Sofía (1999)
The present article exposes the results of a psychometric study of the Interpersonal Reactions Inventory of de Grossarth-Maticek y Eysenck in the spanish version, in the Sandín, Chorot and Navas (1992) investigation; and expose the characteristics to fund in our population to defined for the diagnose prevail and the association between the sex, age and speciality entering with the diagnose of six personality types of SIRI. The SIRI with may be useful people with cancer and coronary heart desease-prone psícologícal to proportion six personality types.